1985
DOI: 10.1007/bf01806050
|View full text |Cite
|
Sign up to set email alerts
|

Menadione sodium bisulphite: A promising plant growth regulator

Abstract: Abstract. Menadione sodium bisulphite (MSB) increased the growth of tomato plants and alfalfa callus and stimulated rooting of mungbean cuttings.Investigations into its effect on auxin metabolism resulted in decreased activities of the enzymes involved in IAA oxidation in tomato plants. The levels of IAA were increased by about 3 to 4 fold following application of MSB to tomato, cucumber, corn and capsicum plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Menadione sodium bisulfite (MSB) is a vitamin K3 derivative known to be a growth regulator ( Rama Rao et al, 1985 ). Borges et al (2003a) found that MSB protects rape plants ( Brassica napus ) from the fungus Leptosphaeria maculans by stimulating ROS production, but without inducing PR1 .…”
Section: Priming By Natural Compoundsmentioning
confidence: 99%
“…Menadione sodium bisulfite (MSB) is a vitamin K3 derivative known to be a growth regulator ( Rama Rao et al, 1985 ). Borges et al (2003a) found that MSB protects rape plants ( Brassica napus ) from the fungus Leptosphaeria maculans by stimulating ROS production, but without inducing PR1 .…”
Section: Priming By Natural Compoundsmentioning
confidence: 99%
“…vitK3 is also known as menadione, a compound that has been isolated from fungi and phanerogams (35), where it was first studied as a plant regulator (36). The function of menadione in the defense against plant pathogens has been shown in several studies (37)(38)(39).…”
Section: Figmentioning
confidence: 99%
“…MSB, first studied as a plant growth regulator (Rama-Rao et al, 1985), has been widely demonstrated to function as plant defense elicitor against several pathogens in a number of different plant species (Borges et al, 2003, 2004, 2009; Liu et al, 2006; Pushpalatha et al, 2007; ShengYi et al, 2007). Changes in gene expression in response to 0.2 mM MSB at different time-points post-treatment, using microarray technology, show that MSB leads to a unique molecular mark by inducing differentially the expression of 158 genes.…”
Section: Msb: a Novel Priming Agentmentioning
confidence: 99%